AVANÇO PARA A REGULARIZAÇÃO FUNDIÁRIA? UMA ANÁLISE COMPARATIVA DAS LEIS 11.977/2009 E 13.465/2017 (REURB), A PARTIR DO ESTUDO DE CASO DE SUAS APLICAÇÕES NO LOTEAMENTO SANTA CRUZ, LINHARES-ES - Grazziotti, Adriano Giacomin (2022)
The great demand for housing, coming from the population attracted by the economic development of the municipalities, linked to an inefficient housing policy, results in urban occupation, often without a proper planning. In the context of illegal occupations, there is an institutional effort involving public authorities, including the Judiciary System, to create mechanisms that enable the land tenure regularization of settlements, such as Federal Law n° 13.465/2017 (‘Reurb’), which amended Law n° 11.977/2009 ‘(Minha Casa Minha Vida’ Program). However, the controversial nature of the Reurb Law, added to its still recent implementation, may lead to inadequate use by municipal technical teams, making it an ineffective urban tool and, consequently, going against the original objectives. Also, the isolated application of the Reurb Law can promote mere titling, without adequate maintenance of the urban infrastructure, raising the value of the land, without effectively changing the reality of the residents. In order to better understand the changes brought about by the Reurb Law, the research aimed to analyze the application of that law in land regularization in the Santa Cruz allotment, in Linhares-ES. The territorial scope of the research contemplates a reality of illegal occupation by low-income people, who acquired the lot through a donation from the municipal government. Still, Linhares replicates the scenario of socio-spatial inequalities, frequent in the national territory, with development based on real estate speculation. The large amount of informal occupations is a weakness observed in the municipality, denying citizens the right to the city. This research is justified by the approach of an important instrument of Urban Planning and also by the need to identify its weaknesses and contribute to the better application of the Reurb Law. As methodological procedures, it was stipulated: a) a brief bibliographic review on illegal occupations and socio-spatial inequalities in Brazil; b) analysis of legislation (Federal Laws n° 13.465/2017 and n° 11.977/2009); c) the reading of the study territory, based on the information obtained by aerial photogrammetric survey, photographic records and documents provided by the Land Regularization Commission of the municipality; and d) the analysis of the regularization process of the Santa Cruz allotment and reflection on the ability of the Reurb Law to guarantee adequate urban conditions. As a result, it was observed the ratification of the signs of an exclusive urbanization process in the region and, from these, an overview was elaborated about the losses and gains arising from the application of the Reurb Law regarding the urbanimprovement in the regularized area. Possibilities for minimizing the problems arising from irregular occupation were also indicated, through the application of the Reurb Law. It was identified that, even if the Reurb Law contributes to the reduction of bureaucracy in Land Regularization, there are still legal aspects to be improved, such as the classification of the Reurb by the executive branch, the regularization of buildings and the schedule for the execution of works and stages of Land regularization. In addition, it is suggested to consider partnerships between City Hall and educational institutions, as a way of improving the dynamics of Land Regularization.